Challenges associated with using extracellular vesicles as biomarkers in neurodegenerative disease - Couch, Y (Taylor and Francis, 2023)
Introduction: The hunt for new biomarkers – for the diagnosis of subcategories of disease, or for the monitoring of the efficacy of novel therapeutics – is an increasingly relevant challenge in the current era of precision medicine. In neurodegenerative research, the aim is to look for simple tools which can predict cognitive or motor decline early, and to determine whether these can also be used to test the efficacy of new interventions. Extracellular vesicles (EVs) are thought to play an important role in intercellular communication and have been shown to play a vital role in a number of diseases. Areas Covered: The aim of this review is to examine what we know about EVs in neurodegeneration and to discuss their potential to be diagnostic and prognostic biomarkers in the future. It will cover the techniques used to isolate and study EVs and what is currently known about their presence in neurodegenerative diseases. In particular, we will discuss what is required for standardization in biomarker research, and the challenges associated with using EVs within this framework. Expert Opinion: The technical challenges associated with isolating EVs consistently, combined with the complex techniques required for their efficient analysis, might preclude ‘pure’ EV populations from being used as effective biomarkers. Whilst biomarker discovery is important for more effective diagnosis, monitoring, prediction and prognosis in neurodegenerative disease, reproducibility and ease-of-use should be the priorities.